TI_GERICHTE 52.2021.216 vom 28. April 2021 , Ordine di monitoraggio e di consolidamento e ripristino di un'opera muraria - TI Tribunale d'appello (2021)
Ordine di monitoraggio e di consolidamento e ripristino di un'opera muraria